Synergistic reinforcement of PVA films with boric acid and nano-silica for high-barrier food packaging - Xinyu Xu; Siqi Xie; Baoying Shi; Di Wu; Yu Lin; Qiaohui Zhi; Yufeng Wang; Haiyan Song (Polymer Testing)
The increasing environmental crisis caused by the extensive use of disposable plastics highlights the pressing demand for sustainable options. This research investigates an innovative method for enhancing the traits of polyvinyl alcohol (PVA) through the addition of boric acid (BA) as a crosslinking agent, along with γ-aminopropyl triethoxysilane modified nano-silica (NS) to refine the polymer matrix. The research focuses on the PVA/BA/NS composite film, examining its chemical structure, surface morphology, thermal stability, mechanical strength, gas barrier properties, surface wettability and UV-blocking ability. The results demonstrate that the overall performance of the composite film is significantly enhanced through the synergistic effects of boric acid (BA) and NS, achieved via crosslinking, nanofiller reinforcement, and structural optimization. The PVA/BA/NS composite films shown notable improvements in oxygen, water vapor barrier qualities, and mechanical strength. Furthermore, the addition of nano-silica greatly improved the films' surface hydrophobic qualities, improving their suitability for food packaging. Notably, the tensile resistance of the composite film improved by about 60 % relative to the PVA film, exceeding the findings of comparable research. Additionally, oxygen barrier performance improved by approximately 68 %, highlighting a significant enhancement. Furthermore, it was noteworthy that UV-blocking ability of the composite film had also been markedly enhanced. These improvements are essential for developing food packaging materials that offer better protection and longer shelf life for perishable products, while maintaining quality and safety for consumers. The results convincingly indicate that the environmentally friendly composite films created in this research possess considerable promise for use in food packaging applications.